BISPHENOL A INTERFERES WITH SYNAPTIC REMODELING - Hajszan, Tibor (2010)
The potential adverse effects of Bisphenol A (BPA), a synthetic xenoestrogen, have long been debated. Although standard toxicology tests have revealed no harmful effects, recent research highlighted what was missed so far: BPA-induced alterations in the nervous system. Since 2004, our laboratory has been investigating one of the central effects of BPA, which is interference with gonadal steroid-induced synaptogenesis and the resulting loss of spine synapses. We have shown in both rats and nonhuman primates that BPA completely negates the ~70–100% increase in the number of hippocampal and prefrontal spine synapses induced by both estrogens and androgens. Synaptic loss of this magnitude may have significant consequences, potentially causing cognitive decline, depression, and schizophrenia, to mention those that our laboratory has shown to be associated with synaptic loss. Finally, we discuss why children may particularly be vulnerable to BPA, which represents future direction of research in our laboratory.